Improving the Acceptability of Human Papillomavirus Vaccines Among Men Who Have Sex With Men According to the Associated Factors: A Systematic Review and Meta-analysis - Yang Zhao; Xiaoli Xin; Huiwen Deng; Junjie Xu; Wenjia Weng; Ming Zhang; Juan Li; Yanqing Gao; Xiaojie Huang; Cuie Liu; Cuie Liu (Frontiers Media S.A., 2021)
Objectives: To investigate the acceptability of human papillomavirus (HPV) vaccination among men who have sex with men (MSM) and its associated factors.Methods: We searched studies written in English in PubMed, EMBASE, and Web of Science with no geographical or time restrictions. We evaluated the quality of the included literature. We calculated the pooled acceptability and performed meta-analysis of selected studies, including factors associated with the acceptability among MSM, using Review Manager (v5.3).Results: The acceptability among the 15 studies (n = 8,658) was 50% (95% CI: 0.27-0.72). The meta-analysis of seven articles (n = 4,200) indicated that having a college or higher degree (OR = 1.62, 95% CI: 1.35-1.95), disclosure of sexual orientation to healthcare professionals (HCPs; OR = 2.38, 95% CI: 1.47-3.86), vaccination with at least one dose for hepatitis A or B (OR = 2.10, 95% CI: 1.42-3.10), awareness of HPV (OR = 1.85, 95% CI: 1.21-2.83), knowledge of HPV (SMD = 0.28, 95% CI: 0.16-0.39), perceived susceptibility to HPV infection (SMD = 0.31, 95% CI: 0.11-0.50), and perceived severity of HPV-related disease (SMD = 0.40, 95% CI: 0.28-0.51) can promote acceptance of HPV vaccines. Meanwhile, people who have had unprotected anal sex or have more sex partners tend to have low acceptance of HPV vaccines.Conclusions: HPV education should be actively promoted according to the factors that influence the acceptability of HPV vaccines among the MSM population. HPV education should be especially aimed at people with low academic qualifications and people with risky sexual behaviors, and should emphasize the aspects of susceptibility to and severity of HPV-related disease. More intervention trials should be conducted to increase the credibility of the results.